ANALISIS KESIAPSIAGAAN PERAWAT INSTALASI RAWAT INAP KELAS 3 TERHADAP BENCANA KEBAKARAN DI RUMAH SAKIT X KOTA SEMARANG - Astari Sari Nastiti; Hanifa Maher Denny; Bina Kurniawan (Jurnal Kesehatan Masyarakat (Undip), 2017)
Preparedness of fire hazard has an important part to be a first step in minimizing losses due to fire. One of those places which have a risk to be burned is hospital. Hospital X have many potential hazards at third class of inpatient installation such as utilization of electricity and utilization of pressured gas cylinder. The purpose of this research was to evaluate nurses preparedness at third class of inpatient installation, room N1, about fire hazard in hospital x Kota Semarang. This was a qualitative research with in depth interview. The subject of this research  consisted  of  six  peoples  as  the  main  informants  and  three  peoples  as  the triangulation informants with purposive sampling as the sample technique. The result showed that nurses at third class of inpatient installation have a good knowledge and attitude about fire  hazard,  Hospital  X  have  a  policy and  standard  operational  procedure  relate  to  fire prevention, HSE section make a fire response plan and fire extinguisher, hydrant, sprinkler, detector, alarm is available in this hospital. Nurses have been trained on fire prevention once in every 6-12 months. Hospital X should do a re-socialization about policy and SOP of fire prevention, and organize the simulation once in a year.